Will Grayson, Will Grayson - Green, John 1977-; Levithan, David (New York Speak, 2011)
When two teens, one gay and one straight, meet accidentally and discover that they share the same name, their lives become intertwined as one begins dating the other's best friend, who produces a play revealing his relationship with them both.
Keywords: Interpersonal relations -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Homosexuality -- Juvenile fiction; Overweight persons -- Juvenile fiction; Theater -- Juvenile fiction; Names, Personal -- Juvenile fiction; Interpersonal relations -- Fiction; Dating (Social customs) -- Fiction; Homosexuality -- Fiction; Overweight persons -- Fiction; Theater -- Fiction; Names, Personal -- Fiction; Chicago (Ill.) -- Juvenile fiction; Chicago (Ill.) -- Fiction